AmpC Beta-Lactamases Detection and Genetic Analysis in Gram Negative Urinary Isolates from Six Districts of Bangladesh (Central Medical College Journal, 2026)
Background: Gram negative bacteria produce AmpC beta-lactamases (AmpCs) becoming a major therapeutic challenge. So, among multidrug resistant bacteria, AmpCs producer’s identification by reliable procedure as well as AmpCs encoding genes detection is essential. Objective: This study was carried out to identify AmpC beta-lactamases producing gram negative bacteria isolated from urine through two convenient methods and to detect plasmid carried AmpC beta-lactamases genes by multiplex PCR from September, 2018 to August, 2019. Methodology: In total, 187 isolates were collected from UTI patients of six district areas in Bangladesh. After re-identification, Gram negative isolates were tested for drug resistance against common antimicrobial drugs in microbiology laboratory of BIRDEM General Hospital, Dhaka. Cefoxitin was assessed as primary screening markers for detection of AmpCs production. As a confirmation test, Modified three dimensional test (MTDT) and AmpC disc test were compared. Plasmid carried AmpC β-lactamases genes (blaCIT, blaDHA, blaACC, blaEBC, blaMOX, blaFOX) were detected by multiplex PCR. Results: Among the total 187 isolates, 181 (91.8%) were gram negative and 6 (9.2%) were gram positive bacteria. Among 181 gram negative bacteria, 37 (20.4%) isolates were cefoxitin resistant of which AmpC beta-lactamases were detected in 18 (48.6%) by AmpC Disc Test and MTDT separately. Among urinary isolates, blaDHA and blaCIT were predominant genes. AmpCs producers were detected among 16% gram negative bacteria from community acquired UTI. Conclusion: Demonstration of AmpCs producers among uropathogenic isolates and AmpCs genes in significant number from this study indicate prevalence of AmpCs producing bacteria causing UTI and transmission of their resistance genes have increased that signify detection of AmpCs producers by a potential but convenient method will ensure physician to give appropriate antibiotic regimens.Central Medical College Journal Vol 9 No 2 July 2025 Page: 96-104